Morphological and cultural characteristics of Colletotrichum isolates from Hevea brasiliensis - Kumar A; Jacob C K; Joseph A (Indian Journal of Natural Rubber Research, 2002)
The morphology of conidia and growth rate of isolates of the fungus causing raised, anthracnose and papery lesions of Colletotrichum leaf disease on rubber were compared. The isolates produced morphologically uniform conidia on potato dextrose agar (PDA). Conidial shape was more useful than size in differentiation of isolates. Growth rate of the isolates from raised lesions was significantly lower than that from anthracnose and papery lesions. The latter two appeared to be similar. In general, the isolates from raiseed lesions produced pink pigmentation on PDA while those from anthracnose and papery lesions produced grey pigments. The isolates from raised lesions were of Colletotrichum acutatum, distinct from anthracnose and papery lesion isolates which were of C. gloeosporioides.
Keywords: Colletotrichum acutatum; Colletotrichum acutatum; Colletotrichum gloeosporioides; Colletotrichum gloeosporioides; Gloeosporium alborubrum; Gloeosporium alborubrum; Glomerella cingulata; Glomerella cingulata; Hevea; Hevea; Taxonomy; Taxonomy; Variability; Variability